Evaluation of the efficacy of wrist arthroscopic surgery for aseptic necrosis of lunate bone - Xiao‐Feng Teng; Hui‐Zong Yuan; Hong Chen (Orthopaedic Surgery, 2022)
Objective To explore the use of wrist arthroscopy for treatment of aseptic necrosis of lunate bone and its curative effect. Methods From March 2012 to January 2016, 12 patients with aseptic necrosis of lunate bone underwent necrotic lunate bone extirpation assisted by wrist arthroscopy, and the scaphocapitate joint treated with fusion‐stabilization were selected. Among these patients, 10 patients were male and two patients were female. The age of these patients ranged from 25 to 42 years old, with an average age of 32 years old. These lesions were located in the right hand in eight patients, and in the left hand in four patients. Lichtman stage: stage IIIA in two patients, and stage IIIB in 10 patients. All patients were diagnosed by anterior lateral radiographs and magnetic resonance imaging (MRI). From the second day after the surgery, patients underwent active motion for the metacarpophalangeal joint and interphalangeal joints. When the X‐ray film indicated that the fracture had healed, patients began to resume their daily activities and work. After surgery, the plain films of all planes, including the axial plane of the scaphoid, were taken every month, until fracture healing. All patients were followed up for a mean duration of 8 months, and the Mayo wrist score was used to assess the range of motion of the wrist joint and grip force during the follow‐ups for objective function evaluation. Results Fracture healing was obtained in all patients within 9–12 weeks after the operation, and average healing time was 10 weeks. The duration of follow‐up ranged between 6–14 months, and the mean duration was 8 months. According to the modified Mayo wrist score, the objective function of the wrist joint was evaluated as follows: flexion and extension range of the wrist joint was 40°–110°, with an average of 105°, which was 80% of that of the unaffected side. Radioulnar deviation was 45°‐80°, with an average of 55°, which was 82% of that of the unaffected side. Grip force was 25–48 kg, with an average of 40 kg, which was 84% of that of the unaffected side. The modified Mayo wrist score was good in eight patients, acceptable in three patients, and poor in one patient. Conclusions Wrist arthroscopy is an effective and feasible tool for the treatment of aseptic necrosis of the lunate bone, and the right kind of surgical procedure should be selected for different stages of the disease, and wrist arthroscopy is applied timely, in order to achieve the desired therapeutic effect.